Comparing the biopsy strategies of prostate cancer: a systematic review and network meta-analysis - Yiqi Huang; Cailiu Wei; Fenjuan Chen; Yanling Zhang; Feifei Pu (BMC Cancer)
Abstract The introduction of three kinds of magnetic resonance imaging-guided prostate biopsies (MRI-PB) has changed the paradigm regarding prostate biopsies (PB). We aimed to compare and rank PB strategies to provide the latest evidence of PB option for prostate cancer (PCa) diagnosis. We searched PubMed, the Cochrane Library Central, Scopus, Embase and the reference lists of relevant articles for randomized controlled trials published up to Dec, 2024, of different PB strategies. Finally, 24 randomized trials were included. Eleven PB strategies published were considered. For overall PCa detection rates exclusively previously negative biopsy patients, we found robust improvements of 3.92 (95% CI: 2.17–6.41) for MRI-cognitive- and 1.78 (95% CI: 1.02–3.07) for MRI/TRUS- compared to TRUS(10–12)-PB. For PCa detection when prostate volume ≤ 50 mm3, only MRI/TRUS- was significantly effective than TRUS(10–12)-PB (OR 1.78, 95% CI: 1.0–2.89). Our study indicated that MRI-cognitive-PB was associated with better overall PCa detection rates compared with TRUS(10–12)-PB, but it had no remarkable advantages in csPCa and ciPCa detection. More head-to-head comparisons of MRI-PB techniques are needed in the future.